Improvements of a Radioimmunoassay for Measurement of Viral Antibody in Human Sera - Patterson, William R. (1975)
Modifications were made which increased the sensitivity of a solid-phase radioimmunoassay for serum antibody to human herpesviruses. Quantitation of antibody can be accomplished by referring to standard curve titrations.